Theoretical Framework for Effective Communication Processes for the Agile Project Management Approach in the UAE Utility Sector - Afifi, Mutasim (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)